THE COMPARATIVE ANALYSIS OF STATE DEBT AND ITS MANAGEMENT - Audra Visockaite; Daiva Deimantaite Gedmintiene (European Scientific Journal, ESJ, 2014)
Purpose - Effective management and optimal cost of a state debt are relevant to every nation.Since the recession the management of a state debt has become increasingly important to the Republic of Lithuania.Significant liabilities had to be made in pursuance to cover up a budget deficit. Therefore, the ratio of the state debt and GDP haveincreased more than twice.. In the future, refinancing previous debts is to remain a keygoal ofborrowing. Consequently, the effective management of the state debt will remain a relevant topic in Lithuania and other states of the EU for a long time to come. In the past state debt grew mainly at times of threat to the national security or recession of economics. Borrowing is inevitable in many countries in order to stimulate the growth of national economy.When state’s expenditure exceeds it’s income, the state is forced to cover up the resulted difference most frequently with borrowed funds.Debts and other financial liabilities caused by such borrowing in state’s name forms the national debt.The government is able to finance and support certain branches of economy and social groups, thus pursuing it’s political objectives, by controlling the national debt and taking over it’s liabilities. State’s borrowing demand is a sum of government’s expenditure formed over budget year, which is expedted to be financed borrowed funds. This article analizes borrowing demands of Lithuania and other Baltic states and the factors determining their state debt management. One of the main methods of satisfy government’s demand to borrow funds is by emmiting government securities. Design/methodology/approach - analyses of the scientific literature Findings and originality –borrowing in name of the state maintains an important influence on strengthening it’s financial systems and supplying them with necessary funds, while available interior recourses are limited. State debt management is an integral part of general state economy politics. Research type - theoretical analysis